Social network effects on consumer willingness to pay for biofortified crops - Muange, Elijah N.; Oparinde, Adewale (International Food Policy Research Institute, 2018)
This study investigated the effects of social networks on consumer willingness to pay (WTP) for two high-iron bean (HIB) varieties (HIB-A and HIB-B) using data collected from 572 farmers in rural Rwanda. The study used the Becker-DeGroot-Marshak mechanism to elicit consumer WTP in the absence and presence of radio messages providing positive and negative frames of information on nutritional benefits of HIB varieties at different frequencies. Instrumental variable and random effects models were used to assess the determinants of WTP.